Continuous assays of glutaminyl cyclase: from development to application. Issue 2 (2004) - Schilling Schilling, Stephan Stephan; Demuth Demuth, Hans-Ulrich Hans-Ulrich
Abstract : Glutaminyl cyclase (QC, EC 2.3.2.5) catalyses the formation of pyroglutamyl residues from glutamine at the N-terminus of peptides and proteins. In previously applied assays, QC activity was determined by either analysing the products formed using HPLC coupled with photometric or fluorometric detection, radioimmunoassay, or by detecting the release of ammonia spectrophotometrically. Although these methods are sensitive, they are all discontinuous and therefore time-consuming and laborious. To conduct a detailed kinetic investigation of QC catalysis, we developed coupled continuous assays suitable for microplates which allow now convenient determination of QC activity. The methods either use pyroglutamyl aminopeptidase or glutamate dehydrogenase as auxiliary enzymes, which results in the liberation of chromophores or fluorophores such as p NA, AMC, β NA or in the conversion of the chromophore NADH/H + into NAD +, respectively. The assays were applied in various enzyme isolation and characterisation studies, using crude protein solutions as well as purified enzyme in pH-dependence, substrate and inhibitor specificity investigations. Depending on the respective analytical task, both assays complement each other. Therefore, different enzymatic properties could be explored in more detail. Since the employed strategy of assay development could be of interest also for the analysis of other enzymes, the methods are described here in a comprehensive manner.